Dual-synergistic effects of citric acid on atmospheric leaching of manganese ores - Widi Astuti; Rofiek Mufakhir, Fika; Iman Supriyatna, Yayat; Daulay, Amru; Setyadji, Moch.; Sofiana Dewi, Jilda (Jurnal Rekayasa Proses, 2025)
In the current study, a leaching of manganese from Indonesian manganese ores using citric acid as leaching reagent without the addition of reducing agent was investigated. Citric acid was being used as a leaching reagent and reducing agent at same time due to its reducing power. Several leaching parameters were investigated to obtain the optimum condition of citric acid leaching of manganese from those manganese ores. Low grade manganese ores from two mining areas in Indonesia contained 36.77% Mn (WK ore) and 12.5% (TG ore) with different mineral types can be leached using citric acid as leaching reagent without addition of reducing agent. The optimum manganese recovery was obtained at around 76% and 69% respectively for WK ore and TG ore with citric acid of 1M, 5% of pulp density, 150 rpm of shaker speed, 30oC of leaching temperature, 1 hour of leaching period, and <75 µm of ore particle size. This condition was also selective for iron recovery leaching. This experiment proves that citric acid has a dual-synergistic effect as an effective leaching reagent and reducing agent at the same time for manganese leaching from manganese ores.